Open Conjunctival Approach for Sub-Tenon's Xen Gel Stent Placement and Bleb Morphology by Anterior Segment Optical Coherence Tomography. Issue 11 (November 2021) - Dangda, Sonal; Radell, Jake E.; Mavrommatis, Maria A.; Lee, Rachel; Do, Anna; Sidoti, Paul A.; Panarelli, Joseph F.
Abstract : Précis: Sub-Tenon's implantation of the Xen Gel stent resulted in significant intraocular pressure (IOP) lowering along with a low rate of postoperative bleb needling, and a favorable bleb morphology on anterior segment optical coherence tomography (AS-OCT). Purpose: The aim was to assess clinical outcomes and bleb morphology following sub-Tenon's implantation of the Xen Gel Stent. Methods: The medical records of patients who underwent sub-Tenon's Xen Gel Stent implantation with intraoperative mitomycin-C through an open conjunctival approach were reviewed. Postoperative IOP and number of glaucoma medications at 1, 3, 6, 9, and 12 months were assessed. Bleb morphology was analyzed at various timepoints using AS-OCT (Topcon DRI OCT version 1.1.1). Results: Twenty-six eyes were included in the study. Mean age was 69.4±8.0 years. Mean preoperative IOP was 28.1±7.8 mm Hg on an average of 3.5±0.9 glaucoma medications. Mean IOP at postoperative month 12 (n=23 eyes) was 12.9±4.0 mm Hg ( P <0.01) on an average of 0.3±0.6 ( P <0.01) glaucoma medications. Three eyes (12%) required postoperative needle revision. Bleb morphology in the early postoperative period (⩽3 mo) was characterized by multiple small subconjunctival microcysts on AS-OCT. At the intermediate (6 to 12 mo) and long-term (>12 mo) timepoints, reduction in microcysts with multiple internal parallel layers of aqueous flow and a uniform pattern were more frequently noted. All functional blebs were characterized by the presence of a posterior episcleral fluid lake. Failed blebs showed absence of aqueous humor around the distal end of the microshunt. Conclusion: Following an open conjunctival approach, sub-Tenon's placement of the Xen Gel Stent with significant IOP lowering was achieved. In eyes with good shunt function, bleb morphology by AS-OCT showed a posterior episcleral fluid lake similar to findings following trabeculectomy.